Defining optimal electrospun membranes to enhance biological activities of human endometrial MSCs - An, Jiangru; Ma, Tianyi; Wang, Qiuhua; Zhang, Jinyi; Santerre, J. Paul; Wang, Wenshuang; Ma, Peng; Zhang, Xiaoqing (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionHuman endometrial mesenchymal stem cells (H-EMSCs) can inhibit endometrial fibrosis and repair damaged endometrium. However, direct cell injection into dam-aged endometrium shows limited cell survival. Cell seeding onto biomaterial-based electrospun membranes could improve H-EMSCs’ survival and prolong their stay at the damaged endometrium. Polycaprolactone (PCL), silk fibroin (SF) and hyaluronic acid (HA) are synthetic or natural biomaterials used by the biomedicine field, however, their effects on the biological activities of H-EMSCs remain unclear.MethodsIn this study, CD90+CD73+CD45− H-EMSCs were extracted from human endometrium and H-EMSCs showed enhanced adhesion, proliferation on PCL-HA vs. PCL, PCL-SF, establishing the potential of the composite to address cell survival issues.ResultsH-EMSCs cultured on PCL-HA showed decreased IL-6 gene expression and increased IL-10, VEGFA, TGF-β gene expression vs. PCL-SF, establishing the potential to create a favorable micro-environment for generating vascularized endometrial tissues. PCL, PCL-SF, PCL-HA all supported CD90 and Meflin expression of the seeded H-EMSCs, establishing PCL as a platform to form enhanced biomaterial composites for endometrial repair in the future.DiscussionThis study provided significant evidence sup-porting the potential of appropriately tailored composites of PCL and HA to moder-ate inflammation and wound-healing, which can be applied for endometrial tissue repair and regeneration.